2021
DOI: 10.1177/01945998211004255
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infectivity in Patients Undergoing Tracheotomy With COVID‐19: A Preliminary Study

Abstract: Objective To establish the presence of live virus and its association with polymerase chain reaction (PCR) positivity and antibody status in patients with COVID-19 undergoing tracheotomy. Study Design Prospective observational study. Setting Single institution across 3 hospital sites during the first wave of the COVID-19 pandemic. Methods Patients who were intubated for respiratory wean tracheotomy underwent SARS-CoV-2 PCR nasal, throat, and endotracheal tube swabs at the time of the procedure. These were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A study reporting on otolaryngologists who contracted COVID-19 noted that disease transmission can occur via tracheostomy . Another recent study demonstrated low rates of SARS-CoV-2 transmission within tracheostomy irrespective of polymerase chain reaction status . Overall, while tracheostomy has not been demonstrated to be a high-risk procedure for SARS-CoV-2 transmission, further studies are needed to establish the role of timing in viral transmission within HCPs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reporting on otolaryngologists who contracted COVID-19 noted that disease transmission can occur via tracheostomy . Another recent study demonstrated low rates of SARS-CoV-2 transmission within tracheostomy irrespective of polymerase chain reaction status . Overall, while tracheostomy has not been demonstrated to be a high-risk procedure for SARS-CoV-2 transmission, further studies are needed to establish the role of timing in viral transmission within HCPs .…”
Section: Discussionmentioning
confidence: 99%
“…Recent directions in determining the risk of infectivity in patients with COVID-19 have been moving toward relying on the duration since the first positive RT-PCR test result or first date of symptoms . A recent publication has suggested that antibody titers may also serve as a useful measure for assessing infectivity in the tracheostomy population . It remains unclear how the effects of vaccination and variant SARS-CoV-2 strains will affect these evolving considerations.…”
Section: Discussionmentioning
confidence: 99%